Upaya Pengawasan Orang Tua terhadap Penggunaan Smartphone pada Anak melalui Metode 3 P - Alwin Widhiyanto; Yulia Rachmawati H (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
In the current era of globalization, advances in information media and technology are felt by almost all levels of society. One manifestation of technological development is smartphones. Smartphones really attract children's attention and interest, so they are one of the factors in increasing the percentage of children using smartphones. A very sensitive period of child development is the age of 1-5 years, so it is often called the golden age. The aim of this Community Service is to increase knowledge and understanding about the importance of the role of parents at home in limiting the use of smartphones so that children can achieve their growth and development process. This activity is carried out in the form of Health Education through counseling, lectures, discussions and questions and answers (counseling). The target of the activity was parents (mothers) whose children attended the One Roof Kindergarten in Ketompen Village, totaling 41 participants. The material provided is about the impact of smartphone use (Positive and Negative) and how parents monitor smartphone use through the 3 P method which includes Understanding, Limiting and Controlling. The result of this activity was that the majority of participants knew and understood how to supervise children when using smartphones.